Presence and infectivity of SARS-CoV-2 virus in wastewaters and rivers - Rimoldi, Sara Giordana; Stefani, Fabrizio; Gigantiello, Anna; Polesello, Stefano; Comandatore, Francesco; Mileto, Davide; Maresca, Mafalda; Longobardi, Concetta; Mancon, Alessandro; Romeri, Francesca; Pagani, Cristina; Cappelli, Francesca; et al. (The Science of the total environment, 2020)
The presence of SARS-CoV-2 in raw wastewaters has been demonstrated in many countries affected by this pandemic. Nevertheless, virus presence and infectivity in treated wastewaters, but also in the receiving water bodies are still poorly investigated. In this study, raw and treated samples from three wastewater treatment plants, and three river samples within the Milano Metropolitan Area, Italy, were surveyed for SARS-CoV-2 RNA detection by means of real time RT-PCR and infectivity test on culture cells. SARS-CoV-2 RNA was detected in raw, but not in treated wastewaters (four and two samples, respectively, sampled in two dates). The isolated virus genome was sequenced, and belonged to the strain most spread in Europe and similar to another found in the same region. RNA presence in raw wastewater samples decreased after eight days, probably following the epidemiological trend estimated for the area. Virus infectivity was always null, indicating the natural decay of viral pathogenicity in time from emission. Samples from receiving rivers (three sites, sampled in the same dates as wastewaters) showed in some cases a positivity to real time RT-PCR, probably due to non-treated, or inefficiently treated discharges, or to the combined sewage overflows. Nevertheless, also for rivers infectivity was null. Risks for public health should be limited, although a precautionary approach to risk assessment is here advocated, giving the preliminary nature of the presented data. [Display omitted] •SARS-CoV-2 RNA presence and infectivity in wastewaters and receptors was assessed.•Viral RNA was detectable in the inflow but not in the outflow wastewaters.•Viral RNA was present in receptors due to sewage overflows or inefficient treatment.•SARS-CoV-2 infectivity was null both in wastewaters and receptors.•A precautionary approach in the assessment of contagious risk is advocated.